Ukama Ustawi Monitoring and Reporting Risk Management Plan - Freer, Gordon (2023)
The report presents a concise overview of the risks associated with the Monitoring and Reporting process for Ukama Ustawi, emphasizing the critical role of accurate and reliable data in achieving these objectives through internal monitoring. Emphasizing the importance of data integrity and reliability sets the stage for the subsequent discussion on mitigating risks associated with external data collection.